The nails and diagnosis in homœopathy - Bouko Levy, Michel M. (British Homeopathic Journal, 1993)
The nails are continuously growing structures which reflect many aspects of the body's functions. The anatomy and physiology of the nails is described. Abnormal appearances of the nails are described in terms of: General appearance, form, colour, structural abnormalities and nail biting. The implications of various appearances of the nails of different digits for prescribing are described.
Keywords: Nails; Anatomy; Appearance; Onychophagia; Homœopathic prescribing; Miasm